PENGARUH VARIASI LATIHAN TERHADAP HASIL SHOOTING FUTSAL PESERTA EKSTRAKULIKULER SMP NEGERI 1 SUNGAI RAYA - Farul Farul; Ahmad Atiq; Fitriana Puspa Hidasari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe problem discussed in this study is the provision of training material that is still monotonous less motivating students, the provision of shooting material is still often ruled out by the trainer. The purpose of this study was to determine the Effect of Exercise Variations on Futsal Shooting Results of Extracurricular Participants at SMP Negeri 1 Sungai Raya. The method in this research is an experiment involving two variables. the population of extracurricular participants at Sungai Raya 1 Junior High School was 25 students, sampling using the Saturated Sampling Method, the researchers took all of the population. This research technique uses tests and measurements, namely tests with a shooting measurement instrument lattice in a futsal game. Data analysis using t-test formula. The results of this study indicate there is an effect of Exercise Variations on the Futsal Shooting Results of Extracurricular Participants in SMP Negeri 1 Sungai Raya. This can be proven based on the calculation results, where the ttest value is 10.808> ttable value (1.711), so that the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. This means that there is an influence of Variations in Training Against the Futsal Shooting Results of Extracurricular Participants in SMP Negeri 1 Sungai Raya. Keywords: Exercise Variation, Shooting.